Unrelenting Fear Under Stress: Neural Circuits and Mechanisms for the Immediate Extinction Deficit - Maren, Stephen (Frontiers in Systems Neuroscience, 2022)
Therapeutic interventions for disorders of fear and anxiety rely on behavioral approaches that reduce pathological fear memories. For example, learning that threat-predictive stimuli are no longer associated with aversive outcomes is central to the extinction of conditioned fear responses. Unfortunately, fear memories are durable, long-lasting, and resistant to extinction, particularly under high levels of stress. This is illustrated by the “immediate extinction deficit”, which is characterized by a poor long-term reduction of conditioned fear when extinction procedures are attempted within hours of fear conditioning. Here I will review recent work that has provided new insight into the neural mechanisms underlying resistance to fear extinction. Emerging studies reveal that locus coeruleus norepinephrine modulates amygdala-prefrontal cortical circuits that are critical for extinction learning. These data suggest that stress-induced activation of brain neuromodulatory systems biases fear memory at the expense of extinction learning. Behavioral and pharmacological strategies to reduce stress in patients undergoing exposure therapy might improve therapeutic outcomes.